Peening-induced work hardening gradient and prediction of residual stress for a shot peened structure. (1st November 2022) - Zhou, Jianqiang; Cui, Kun; Sun, Zhidan
Abstract: Peeing-induced work hardening (Peening-WH) gradient generated by conventional shot peening is studied taking into account different shot peening parameters. 316L and TRIP780 steels are considered and respectively described with Johnson-Cook and combined isotropic/kinematic hardening constitutive models. The Peening-WH is characterized by residual isotropic hardening (RIH) and residual kinematic hardening (RKH). The latter is expressed through two RKH parameters δ ∗ and θ ∗ . δ ∗ describes the relative position of the residual stress state and RKH, while θ ∗ describes their orientation, in the deviatoric plane. Results indicate that θ ∗ varies around the value of π in the whole plastically affected region, while δ ∗ presents a small difference in the in-depth variation for the two materials. Impact velocity, incidence angle and coverage barely affect the δ ∗ profiles, while bigger shot can slightly increase the value of δ ∗ for the TRIP780 steel. On this basis, a series of residual stress prediction models are deduced and validated through the analysis of δ ∗ . The prediction of residual stress is further discussed taking into account materials with different hardening behaviours. The approach presented in this paper can be applied not only in reconstruction of work hardening, but also in prediction of residual stress for shot peened structures.